Wage divergence and unemployment: the impact of insider power and training costs - Joan Muysken; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
The US labour market is characterized by a high skill wage mark-up and low unemployment, while the German labour market has a low skill wage mark-up and a high, mainly unskilled unemployment rate. This paper adds an innovative labour supply explanation to the discussion how these distinct labour market equilibria could arise. Skill-biased technological change induces training needs for the employees willing to work in the skilled labour market and increases relative skill demand. In a simple general equilibrium model, this paper shows that skilled insiders in the USA enjoy higher rents and increase the skilled wage mark-up stronger than in Germany in the wake of skill-biased technological change. The reason is that the unskilled outsiders in the USA do not possess a powerful credible threat to improve their position. This is a consequence from higher training and education costs in the USA for unskilled employees and unemployed. In Germany, the lower skill wage mark-up leads to an increased relative skill demand which is not matched by the skill supply and therefore mis-match unemployment arises.
Keywords: O33; J31; J24; 330; Mis-match unemployment; training costs; skill biased technological change; Labour supply; Arbeitslosigkeit; Qualifikation; Humankapital; Technischer Fortschritt; Hochqualifizierte Arbeitskräfte; Weiterbildung; Insider-Outsider-Modell; Ungelernte Arbeitskräfte; Bildungsfinanzierung; Potenzieller Wettbewerb; Theorie; Vergleich; USA